Control measures for pests, species identification, prevention of infestation, preventive measures, and pest management strategies in restaurants - Kuzmenko, Rostislav; Kravchenko, Anatoliy; Vozniuk, Svitlana; Kuzmin, Oleg (My University, 2023)
У статті розглядаються методи, які можна використовувати для попередження, виявлення та знищення шкідників у закладах ресторанного господарства. Особливу увагу приділено шкідникам-комахам. Це є важливим питанням для забезпечення безпеки харчових продуктів і захисту здоров’я споживачів

This article discusses methods that can be used to prevent, detect and destroy pests in restaurants. Special attention is paid to insect pests. This is an important issue for ensuring the safety of food products and protecting the health of consumers
Keywords: кафедра технології ресторанної і аюрведичної продукції; HACCP; шкідники; дератизація; дезінсекція; комахи; контроль; профілактика; pests; deratization; disinsection; insects; control; prevention